Examining a new generation of service provision in a developing country: Opportunities and Challenges of Virtual Library Services in Universities in Uganda - Namugera, Lydia; Bukirwa, Joyce; Okello-Obura, Constant (Qualitative and Quantitative Methods in Libraries, 2024)
There is an overwhelming need for Virtual Library and Information Services (VLIS) due to the revolutionary and innovative use of the Internet, alternate information sources, evolving institutional policies and user needs, and potential disasters like the Covid-19 outbreak that prevented access to physical libraries. This study sought to identify benefits that both users and librarians derive from VLIS usage as well as setbacks limiting VLIS provision and utilization. Mixed methods with a pragmatic research paradigm were adopted. Data from library users and staff from 2 universities, one public and one private were gathered using surveys and interviews, respectively. 394 library users and 8 library staff made up the sample size. VLIS benefits included support with coursework, e-resource remote access, instant response to users' queries, notifications of new library additions, improvement in knowledge and skills, timely access to current information, and wide access to numerous e-resources. Challenges to VLIS entailed reliance on Google, unawareness, frustrations by requests to buy or subscribe to e-resources, poor Internet connectivity, limited Information Literacy (IL) skills, restricted access to e-resources, insufficient infrastructure, high cost of e-resources, poor attitude towards VLIS, lack of digital versions for local resources, and low concentration in virtual IL classes.